Decoding Bank Stocks: Fundamental Analysis for Market Prediction - Maulana, Bintang; Triyunita, Gizka; Tabitha, May Rani; Octaviyani, Risca (Lembaga Riset Mutiara Akbar, 2025)
This study presents a fundamental analysis of three major Indonesian bank stocks—BBCA, BBRI, and BBNI—as of March 2025. Using key indicators such as Price-to-Earnings Ratio (P/E), Price-to-Book Value (P/BV), Dividend Yield, and Return on Equity (ROE), the research evaluates valuation, income potential, and efficiency. Data were based on February 2025 stock prices and 2024 financial projections. Results show BBRI offers the best investment value with a low P/E (10.49x), strong Dividend Yield (7.65%), and solid ROE (18.37%), ideal for income and value investors. BBNI appears undervalued (P/BV 1.27x) with decent yield (5.95%) but lower ROE (12.12%). BBCA maintains premium status with high efficiency (ROE 19.78%) and valuation (P/E 18.85x), suitable for growth-focused investors. Overall, BBRI stands out as the most balanced stock, although sector-specific risks like NPL should be considered. These insights aim to support investor decisions in navigating Indonesia’s banking sector during economic uncertainty.